Microcystin-LR-Exposure-Induced Kidney Damage by Inhibiting MKK6-Mediated Mitophagy in Mice - Xueqiong Yao; Ying Liu; Yue Yang; Yafang Li; Na Hu; Fengmei Song; Fei Yang (Toxins, 2023)
Previous studies have reported that microcystin-LR (MC-LR) levels are highly correlated with abnormal renal function indicators, suggesting that MC-LR is an independent risk factor for kidney damage. However, the evidence for the exact regulation mechanism of MC-LR on kidney damage is still limited, and further in-depth exploration is needed. In addition, the mitochondria-related mechanism of MC-LR leading to kidney damage has not been elucidated. To this end, the present study aimed to further explore the mechanism of mitophagy related to kidney damage induced by MC-LR through in vitro and in vivo experiments. Male C57BL/6 mice were fed with a standard rodent pellet and exposed daily to MC-LR (20 μg/kg·bw) via intraperitoneal injections for 7 days. Moreover, HEK 293 cells were treated with MC-LR (20 μM) for 24 h. The histopathological results exhibited kidney damage after MC-LR exposure, characterized by structurally damaged nephrotomies, with inflammatory cell infiltration. Similarly, a significant increase in renal interstitial fibrosis was observed in the kidneys of MC-LR-treated mice compared with those of the control group (CT) mice. MC-LR exposure caused impaired kidney function, with markedly increased blood urea nitrogen (BUN), creatinine (Cr), and uric acid (UA) levels in mice. Ultrastructural analysis exhibited obviously swollen, broken, and disappearing mitochondrial crests, and partial mitochondrial vacuoles in the MC-LR-treated HEK 293 cells. The Western blotting results demonstrated that exposure to MC-LR significantly increased the protein expressions of MKK6, p-p38, and p62, while the expression of mitophagy-related proteins was significantly inhibited in the kidneys of mice and HEK293 cells, including parkin, TOM20, and LC3-II, indicating the inhibition of mitophagy. Therefore, our data suggest that the inhibition of MKK6-mediated mitophagy might be the toxicological mechanism of kidney toxicity in mice with acute exposure to MC-LR.